Double, triple or quadruple hits? Exploring the impact of cybercrime on victims in the Netherlands - Notté, Raoul (International review of victimology, 2021)
This article explores the impact of online crime victimisation. A literature review and 41 interviews – 19 with victims and 22 with experts – were carried out to gain insight into this. The interviews show that most impacts of online offences correspond to the impacts of traditional offline offences. There are also differences with offline crime victimisation. Several forms of impact seem to be specific to victims of online crime: the substantial scale and visibility of victimhood, victimisation that does not stop in time, the interwovenness of online and offline, and victim blaming. Victims suffer from double, triple or even quadruple hits; it is the accumulation of different types of impact, enforced by the limitlessness in time and space, which makes online crime victimisation so extremely invasive. Furthermore, the characteristics of online crime victimisation greatly complicate the fight against and prevention of online crime. Finally, the high prevalence of cybercrime victimisation combined with the severe impact of these crimes seems contradictory with public opinion – and associated moral judgments – on victims. Further research into the dominant public discourse on victimisation and how this affects the functioning of the police and victim support would be valuable.